Maternal mental health in the workplace (MAMH@WORK): A protocol for promoting perinatal maternal mental health and wellbeing - Costa, J.; Santos, O.; Virgolino, A.; Pereira, M. E.; Stefanovska-Petkovska, M.; Silva, H.; Navarro-Costa, P.; Barbosa, M.; Neves, R. C.; Silva, I. D.; Alarcão, V.; Vargas, R.; et al. (International Journal of Environmental Research and Public Health, 2021)
Women are exposed to increased burden of mental disorders during the perinatal period: 13–19% experience postpartum depression. Perinatal psychological suffering affects early mother-child relationship, impacting child’s emotional and cognitive development. Return-to-work brings additional vulnerability given the required balance between parenting and job demands. The MAternal Mental Health in the WORKplace (MAMH@WORK) project aims to develop and evaluate the effectiveness of a brief and sustainable intervention, promoting (a) maternal mental health throughout pregnancy and first 12 months after delivery, and (b) quality of mother–child interactions, child emotional self-regulation, and cognitive self-control, while (c) reducing perinatal absenteeism and presenteeism. MAMH@WORK is a three-arm randomized controlled trial. A short-term cognitive-behavioral therapy-based (CBT-based) psychoeducation plus biofeedback intervention will be implemented by psychiatrists and psychologists, following a standardized procedure manual developed after consensus (Delphi method). Participants (n = 225, primiparous, singleton pregnant women at 28–30 weeks gestational age, aged 18–40 years, employed) will be randomly allocated to arms: CBT-based psychoeducation intervention (including mindfulness); psychoeducation plus biofeedback intervention; and control. Assessments will take place before and after delivery. Main outcomes (and main tools): mental health literacy (MHLS), psychological wellbeing (HADS, EPDS, KBS, CD-RISC, BRIEF COPE), quality of mother–child interaction, child–mother attachment, child emotional self-regulation and cognitive self-control (including PBQ, Strange Situation Procedure, QDIBRB, SGS-II, CARE-Index), job engagement (UWES), and presenteeism. Intention-to-treat and per-protocol analyses will be conducted; Cohen’s d coefficient, Cramer’s V and odds ratio will be used to assess the effect size of the intervention. MAMH@WORK is expected to contribute to mental health promotion during the perinatal period and beyond. Its results have the potential to inform health policies regarding work–life balance and maternal mental health and wellbeing promotion in the workplace.